SEGMENTASI PASAR DAN PENETAPAN PASAR SASARAN PEMASARAN UDANG GALAH DESA PERING KECAMATAN BLAHBATUH KABUPATEN GIANYAR - ANTARA, MADE; OKA UTARI, ANAK AGUNG (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 1 Februari 2008)
Conducting Large Prawn have very good prospect if supported by correct marketing, in this case which is prawn conducting of the Pering village, Blahbatuh District, Gianyar Regency. To increase the accuracy of marketing, done by market segmentation, which is grouping market become some categories -as according to certain criteria’s. The purpose of these researches is to know market segmentation and targeting of Large Prawn marketing in Pering village. This Location Research is selected by purposive sampling. Variable which has been analyzed in this researches are geographical area variable, type of effort, prawn size, purchasing frequencies and purchasing power. This research was held on May, 10th until June, 20th 2006, those variables have been analyzed with descriptive qualitative method. The prawn marketing mix in Pering village such as: (1). Product; prawn has 4 kind of size which are Jumbo prawn, King Prawn, Prawn, Shrimp. (2). Price; prawn’s price is not profitable to the farmers. (3). Distribution; the prawn distribution into market through a very long channel and complex. (4). Promotion; the prawn of Pering village is known by consumer even though by distributor that known from someone to the other one. The market of large prawn marketing of Pering village divided into five segments according to variable that has been analyzed. The pattern of targeting market selection from agribusiness in Pering village is a selected specialization, which is to choose some market segments objectively, which are each market segments are interesting and adequate, in this case the restaurants or cafe with P (prawn) measure, purchasing frequencies less than 10 times /month and purchasing power between 30 until 70 kg /month that exist in Kuta area. To increase the accuracy of marketing, the farmers and all perpetrators of market have to focus on the market activities and prawn product at the targeting market, but do not overrule the other small market segments, because one day this small market segments will have potency to become wider. For the shake of marketing process fluency, it’s very important to pay attention on farmer’s price by cut market channel and actively involve the farmers in marketing.
Keywords: Market, Segmentation, Targeting, Prawn